In vivo activation of methyl-coenzyme M reductase by carbon monoxide - Zhou, Yuzhen; Dorchak, Alexandria E.; Ragsdale, Stephen W. (Frontiers in Microbiology, 2013)
Methyl-coenzyme M reductase (MCR) from methanogenic archaea catalyzes the rate-limiting and final step in methane biosynthesis. Using coenzyme B (CoBSH) as the two-electron donor, MCR reduces methyl-coenzyme M (CH3-SCoM) to methane and the mixed disulfide, CoBS-SCoM. MCR contains an essential redox-active nickel tetrahydro¬corphinoid cofactor, Coenzyme F430, at its active site. The active form of the enzyme (MCRred1) contains Ni(I)-F430. Rapid and efficient conversion of MCR to MCRred1 is important for elucidating the enzymatic mechanism, yet this reduction is difficult because the Ni(I) state is subject to oxidative inactivation. Furthermore, no in vitro methods have yet been described to convert Ni(II) forms into MCRred1. Since 1991, it has been known that MCRred1 from Methanothermobacter marburgensis can be generated in vivo when cells are purged with 100% H2. Here we show that purging cells or cell extracts with CO can also activate MCR. The rate of in vivo activation by CO is about 15 times faster than by H2 (130 min-1 and 8 min-1, respectively) and CO leads to two-fold higher MCRred1 than H2. Unlike H2-dependent activation, which exhibits a 10-h lag time, there is no lag for CO-dependent activation. Based on cyanide inhibition experiments, CODH is required for the CO-dependent activation. Formate, which also is a strong reductant, cannot activate MCR in M. marburgensis in vivo.